Lifetime prediction of InGaZnO thin film transistor for the application of display device and BEOL-transistors. (April 2018) - Kim, Sang Min; Cho, Won Ju; Yu, Chong Gun; Park, Jong Tae
Highlights: Lifetime prediction model of InGaZnO TFTs for display and BEOL transistors. Lifetime is proportional to the inverse square-root of VGS in the exponential term under high VGS and low VDS . Lifetime is proportional to the inverse of VDS in the exponential term under low VGS and high VDS . Abstract: In this work, the lifetime prediction models of amorphous InGaZnO thin film transistors (a-IGZO TFTs) were suggested for the application of display device and BEOL (Back End Of line) transistors with embedded a-IGZO TFTs. Four different types of test devices according to the active layer thickness, source/drain electrode materials and thermal treatments have been used to verify the suggested model. The device lifetimes under high gate bias stress and hot carrier stress were extracted through fittings of the stretched-exponential equation for threshold voltage shifts and the current estimation method for drain current degradations. Our suggested lifetime prediction models could be used in any kinds of structures of a-IGZO TFTs for the application of display device and BEOL transistors. The a-IGZO TFTs with embedded ITO local conducting layer under source/drain is better for BEOL transistor application and a-IGZO TFTs with InGaZnO thin film as source/drain electrodes may be better for the application of display devices.